2017
DOI: 10.3389/fmicb.2017.00328
|View full text |Cite
|
Sign up to set email alerts
|

There Is a Method to the Madness: Strategies to Study Host Complement Evasion by Lyme Disease and Relapsing Fever Spirochetes

Abstract: Lyme disease and relapsing fever are caused by various Borrelia species. Lyme disease borreliae, the most common vector-borne pathogens in both the U.S. and Europe, are transmitted by Ixodes ticks and disseminate from the site of tick bites to tissues leading to erythema migrans skin rash, arthritis, carditis, and neuroborreliosis. Relapsing fever borreliae, carried by ticks and lice, trigger reoccurring fever episodes. Following transmission, spirochetes survive in the blood to induce bacteremia at the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 72 publications
0
20
0
1
Order By: Relevance
“…The WT strain B31‐A3 and B31‐A3Δ cspZ ‐V were incubated with human or quail serum, or negative control sera that were not expected to kill bacteria (C3‐depleted human serum or heat‐inactivated human or quail serum) for 4 hr. Mouse serum was not tested because mouse complement is highly unstable ex vivo (Caine & Coburn, ; Lachmann, ; Marcinkiewicz et al, ; Ristow et al, ). Consistent with previous findings (Coleman et al, ), we found that nearly 100% of the WT strain B31‐A3 and B31‐A3Δ cspZ ‐V survive in human, quail, and negative control sera (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WT strain B31‐A3 and B31‐A3Δ cspZ ‐V were incubated with human or quail serum, or negative control sera that were not expected to kill bacteria (C3‐depleted human serum or heat‐inactivated human or quail serum) for 4 hr. Mouse serum was not tested because mouse complement is highly unstable ex vivo (Caine & Coburn, ; Lachmann, ; Marcinkiewicz et al, ; Ristow et al, ). Consistent with previous findings (Coleman et al, ), we found that nearly 100% of the WT strain B31‐A3 and B31‐A3Δ cspZ ‐V survive in human, quail, and negative control sera (Figure S7).…”
Section: Resultsmentioning
confidence: 99%
“…Pathogens have developed multiple mechanisms to escape killing by complement (Lambris, Ricklin, & Geisbrecht, ). One such mechanism is the production of complement‐binding proteins to block the formation of complement complexes (Blom, Hallstrom, & Riesbeck, ; Kraiczy, ; Marcinkiewicz, Kraiczy, & Lin, ; Meri, ). Another mechanism is to express complement regulator‐binding proteins, which recruit host complement regulators to the cell surface to degrade active complement complexes (Blom et al, ; Meri, ).…”
Section: Introductionmentioning
confidence: 99%
“…Complement is a central component of the host innate immune system and the first line of defense against bacterial infection. Evasion of the host complement system is essential for Borrelia to successfully establish infection (Caine and Coburn, 2016;Kraiczy, 2016;Marcinkiewicz et al, 2017) (see Sjoberg et al, 2009;Zipfel and Skerka, 2009;Meri, 2016 for more thorough reviews). The complement system is composed of more than 30 proteins and inactive precursors (Zipfel and Skerka, 2009).…”
Section: Lyme Disease Spirochetes Evade the Vertebrate Hosts' Complementmentioning
confidence: 99%
“…It has been hypothesized that the pathogenic microbe cloaks itself with host factors to survive the attack of the host immune system and this might also be the function of the fibrinogen–OspC complex. This strategy might explain the spirochete's ability to persist in the unfriendly blood environment in spite of carrying such an immunogenic protein on its surface . We also observed that OspC has a negative influence on fibrin clot formation in vitro .…”
Section: Discussionmentioning
confidence: 59%
“…Outer surface protein C lipoprotein is abundantly produced during early infection when the Borrelia spirochetes spread in the host bloodstream to reach different tissues and organs. One of the established roles played by OspC refers to the recruitment of some blood components, which facilitates the bloodstream survival of Borrelia during this essential step of the infection . Our in vitro results indicate that fibrinogen might be another blood protein belonging to the OspC interaction network.…”
Section: Discussionmentioning
confidence: 67%